The cryptocurrency participation puzzle - DUCHIN, Ran (Institutional Knowledge at Singapore Management University, 2022)
We show that ongoing zero portfolio weights in cryptocurrency are surprisingly difficult to generate in a standard Bayesian portfolio theory framework. With ten years of prior data, equity market investors would need very pessimistic priors on mean returns to justify never having bought cryptocurrency: -10.6% per month for Bitcoin, and -19.6% per month for a diversified portfolio of cryptocurrencies. Moreover, most priors that involve never purchasing cryptocurrency imply that investors should short cryptocurrency. Optimal absolute weights are generally small but non-trivial (1-5%), frequently positive, and fairly smooth despite returns being volatile. Under a wide range of priors, the certainty equivalent gains from cryptocurrency are comparable to international diversification and exceed the size anomaly. Trading costs (ambiguity aversion, storage, fees) would need to be enormous to justify non-investment, over 21% per year for Bitcoin and 39% for a diversified cryptocurrency portfolio.